INOVASI PENGEMBANGAN PRODUK ABON IKAN TUNA SEBAGAI STRATEGI PENINGKATAN NILAI TAMBAH UMKM PANGAN LOKAL - Andi Hasryningsih Asfar; Leyla Ayu Azkiyah; Uun Uun; Rafa Anargya Ramadhan; Jiddan Muhiza (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
Indonesia, as one of the world’s leading tuna producers, holds significant potential for developing value-added fish-based products. However, coastal SMEs face challenges related to raw material availability, product quality, and marketing strategies. This study aims to analyze the innovation of tuna floss product development as a strategy to enhance the added value of local food SMEs, particularly in Tanjungjaya Village. The main research question addresses how product quality, economic feasibility, and development strategies of tuna floss can strengthen SME competitiveness. A qualitative descriptive method was applied through observation, interviews, documentation, and supported by sensory evaluation, economic analysis, and SWOT mapping. The findings reveal that tuna floss achieved high consumer acceptance (sensory scores >7), favorable nutritional quality (protein 38.5%; moisture 4.2%), and a shelf life of up to six months. SWOT analysis highlights the dominance of strengths and opportunities, while economic analysis indicates the need for cost efficiency or price adjustments. In conclusion, tuna floss development has the potential to increase added value, expand market reach, and reinforce the resilience of coastal SMEs. Future research is recommended to explore flavor innovation, advanced packaging technology, and digital marketing strategies to extend shelf life and broaden market penetration.